THE EFFECT OF SPECIAL AUTONOMY FUND ON ACEH’S ECONOMIC GROWTH - Devita Aryani; Weri (CV. RADJA PUBLIKA, 2024)
The reason for this examination is to break down the impact of Unique Independence reserve (Otsus) to the financial development of Aceh. The model utilized in this examination is straightforward direct relapse by involving time series information for the extended period of 2008 to 2022. Findings of this research show that Otsus fund has a positive and significant effect to the economic growth of Aceh which is 1 percent increasing in Otsus fund will increase 0.32 percent the economic growth of Aceh by assumption that other variables do not change. This shows that Otsus fund has an important role in increasing economic growth of Aceh. Because the role of this Otsus fund in increasing Aceh's economic growth can be optimalized in the future, it is recommended to the Aceh Government to evaluate and review the purpose, allocation, and the using of the Otsus fund for Aceh and Locale/Regions Government.